1998
DOI: 10.1152/ajpcell.1998.275.2.c544
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of protein kinase C-δ increases tight junction permeability in LLC-PK1epithelia

Abstract: The Ca2+-independent δ-isoform of protein kinase C (PKC-δ) was overexpressed in LLC-PK1 epithelia and placed under control of a tetracycline-responsive expression system. In the absence of tetracycline, the exogenous PKC-δ is expressed. Western immunoblots show that the overexpressed PKC-δ is found in the cytosolic, membrane-associated, and Triton-insoluble fractions. Overexpression of PKC-δ produced subconfluent and confluent epithelial morphologies similar to that observed on exposure of wild-type cells to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 60 publications
6
55
0
Order By: Relevance
“…In pulmonary epithelial monolayers, PKC␣ activation modulates TNF␣-induced increase in paracellular permeability (31). Similarly, it has been reported (17,18) that PKC␣ and PKC␦ expression were correlated with tight junctional leakiness in renal epithelial cells. Marano et al (33) reported that phorbol ester increased paracellular permeability in IEC-18 intestinal cells by a mechanism involving translocation of PKC␣ from the cytosolic to membrane compartment and phosphorylation of the tight junctional protein occludin.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In pulmonary epithelial monolayers, PKC␣ activation modulates TNF␣-induced increase in paracellular permeability (31). Similarly, it has been reported (17,18) that PKC␣ and PKC␦ expression were correlated with tight junctional leakiness in renal epithelial cells. Marano et al (33) reported that phorbol ester increased paracellular permeability in IEC-18 intestinal cells by a mechanism involving translocation of PKC␣ from the cytosolic to membrane compartment and phosphorylation of the tight junctional protein occludin.…”
Section: Discussionsupporting
confidence: 65%
“…A substantial body of experimental data indicates that PKC regulates paracellular permeability in epithelial (17,18) and endothelial (31) monolayers. The PKC activators diacylglycerol and phorbol esters increase paracellular permeability and diminish TER (15,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein kinase C activation has been shown to decrease 34,107,116 or increase 106,117,118 paracellular permeability. This suggests a complex signaling pathway at the junctional complex.…”
Section: Serine Threonine Kinasesmentioning
confidence: 99%